1597. Risk Factors for Failure of Primary (Val)ganciclovir Prophylaxis Against Cytomegalovirus (CMV) Infection and Disease in Solid Organ Transplant (SOT) Recipients. (26th November 2018) - Khurana, Mark Poulsen; Lodding, Isabelle Paula; Mocroft, Amanda; Sørensen, Søren Schwartz; Perch, Michael; Rasmussen, Allan; Gustafsson, Finn; Lundgren, Jens
Abstract: Background: Following solid-organ transplantation (SOT), the optimal dose of primary (val)ganciclovir (v(gcv)) prophylaxis against CMV infection is debated, and breakthrough infection and treatment-limiting side effects are frequently seen. Rates and risk factors for CMV prophylaxis breakthrough and premature cessation of prophylaxis for other reasons were investigated in a large cohort of consecutive SOTs. Methods: SOT recipients transplanted (tx) between 2012 and 2016 at Rigshospitalet, and who were initiated on primary prophylaxis ≤14 days post-tx were followed from this time until 90 (±7) days post-tx. A prophylaxis score for each patient/day was calculated during the follow-up time (FUT) (score of 100 corresponding to the manufacturers' recommended dose for a given eGFR; Figure 1). Prophylaxis breakthrough was defined as PCR verified CMV DNA positivity in plasma or BAL (i.e., infection) and premature stop of prophylaxis as >7 days with a score of 0. Time to event and hazard ratios (HR) were estimated with Cox models after adjustment for relevant risk factors. Results: Of 585 SOTs (311 kidney, 117 liver, 106 lung, 51 heart) included, 41 (7%, 95% CI 4.9–9.1%) experienced CMV prophylaxis breakthrough (9/41 [22%, 9.2–34.6%] developed viral resistance to (v)gcv) and 33/585 (5.6%, 3.7–7.5%) ceased prophylaxis for other reasons during the first 90 days after tx. After adjustment for tx type, CMV IgG D+/R− mismatch and increasing % of FUT with a prophylaxis score < 90 were associated with increased risk of breakthrough (HR 4.76 [95% CI 2.38–9.54] P < 0.001 and HR 1.15 [1.04–1.27] P = 0.007/10% longer FUT w/ score < 90 respectively, Figure 2) whereas tx type was not. The main risk factor for stopping prophylaxis for reasons other than breakthrough was lung tx (22.9%, HR 13.4 (vs. kidney SOT) [5.4–33.4]), mainly due to liver or myelotoxicity. Conclusion: SOTs receiving (v)gcv primary prophylaxis doses below the manufacturers' recommended doses according to latest eGFR were at an increased risk of CMV prophylaxis breakthrough, particularly in case of CMV IgG D+/R− mismatch, while 23% of lung tx recipients stopped prophylaxis mainly due to toxicity. Our findings indicate the need to dose adjust (v)gcv according to latest eGFR and preferably use novel, less toxic agents. Disclosures: All authors: No reported disclosures.